Ending the Human Immunodeficiency Virus Pandemic: Optimizing the Prevention and Treatment Toolkits. (24th October 2019) - Eisinger, Robert W; Folkers, Gregory K; Fauci, Anthony S
Abstract: Unprecedented basic and clinical biomedical research advances over the past 4 decades have led to the development of "toolkits" of highly effective interventions for preventing and treating human immunodeficiency virus (HIV). Despite many successes in decreasing the incidence and mortality of HIV, major challenges remain in the goal of ending the HIV pandemic in the United States and globally. Overcoming these challenges will require optimization of the implementation of existing interventions for HIV prevention and treatment together with the continued development of new and innovative approaches that can be readily utilized by individuals with HIV and those at risk of infection. Abstract : Effective toolkits for human immunodeficiency virus (HIV) prevention and treatment have had a major impact on the HIV pandemic. Optimization of the implementation of these existing interventions, along with the development of new interventions are essential to ending this pandemic.